Effect of nanomaterials on arsenic volatilization and extraction from flooded soils. (August 2018) - Huang, Qing; Zhou, Shiwei; Lin, Lina; Huang, Yongchun; Li, Fangjun; Song, Zhengguo
Abstract: Herein, we utilize sequential extraction and high-throughput sequencing to investigate the effects of nanomaterial additives on As volatilization from flooded soils. We reveal that maximum volatilization is achieved in the fourth week and is followed by stabilization. The extent of volatilization decreased in the order of control > nano-zerovalent iron >40-nm hydroxyapatite > nano-Fe3 O4  > 20-nm hydroxyapatite > multilayer graphene oxide > high-quality graphene oxide. The most abundant forms of As in soil corresponded to As-Fe and Al oxides. In soil with low levels of As pollution, the contents of these species increased after treatment with graphene oxides but decreased after treatment with other nanomaterials, with an opposite trend observed for soil with high levels of As pollution. The addition of nanomaterials influenced the activity of soil enzymes, e.g., hydroxyapatites affected the activities of urease and alkaline phosphatase, whereas graphene oxides significantly impacted that of peroxidase ( P  < 0.05). The addition of nanomaterials (which can potentially inhibit microbial growth) affected As levels by influencing the amount of As volatilized from polluted soil. Moreover, As volatilization, enzyme activity, and As speciation were observed to be mutually correlated (e.g., volatilization was negatively correlated to peroxidase activity and the contents of amorphous crystalline hydrous oxides of As-Fe and Al). Graphical abstract: Image 1 Highlights: Effect of nanomaterial additives on As volatilization from soils was investigated. Treatment of As-polluted soil with nanomaterials reduced As volatilization. The observed volatilization order corresponded to control > nFe > nFe3 O4  > HA40  > HA20  > MGO > HGO. Correlations were observed between As volatilization/speciation and enzyme activity. Nanomaterials could inhibit microbial growth in As-polluted soil.